A new multi-layered microwave absorber for wireless appliance using coconut shell-based microwave absorbers / Norsuzila Ya’acob ... [et al.] - Ya’acob, Norsuzila; Awang, Zaiki; Wan Muhammad, Wan Norsyafizan; Mozi, Aiza Mahyuni (Research Management Institute (RMI), 2014)
Microwave absorbers are used for reducing radar detection and overcome the wireless interferences. Carbon is a one of main component in microwave absorbers. Coconut shell activated carbon was used in this project which one type of carbon. Coconut shell powder was mixed with Flaxane-80 as binder in producing microwave absorber samples. Different percentages of carbon content samples were prepared to study the microwave properties. The permittivity of samples increases when the carbon content increases. The single layer absorbers also produced with various of thicknesses. The resonant frequency of single layer absorber goes to lower value when the thickness increases. The single layer exhibits narrow bandwidth characteristic. The two, three and four layer microwave absorber samples were fabricated. The bandwidth of multi-layer absorbers increases when number layer was added.